Author Correction: Immune cell profiling of COVID-19 patients in the recovery stage by single-cell sequencing - Wen, Wen; Su, Wenru; Tang, Hao; Le, Wenqing; Zhang, Xiaopeng; Zheng, Yingfeng; Liu, Xiuxing; Xie, Lihui; Li, Jianmin; Ye, Jinguo; Dong, Liwei; Cui, Xiuliang; et al. (Cell discovery, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.